N = 2 SUSY Abelian Higgs model with hidden sector and BPS equations - Arias, Paola (2015)
In this paper we study a system inspired on certain SUSY breaking models and on more recent Dark Matter scenarios. In our set-up, two Abelian gauge fields interact via an operator that mixes their kinetic terms. We find the extended Supersymmetric version of this system, that also generates a Higgs portal type of interaction. We obtain and study both analytically and numerically, the equations defining topologically stable string-like objects. We check our results using two different approaches.